How Aung San Suu Kyi Can Free Burma from Fear - Lwin, Michael (Columbia Journal of Asian Law, 2011)
Last November, Burma held its first elections in twenty years. Nobel laureate Aung San Suu Kyi was released from house arrest soon after the elections. This paper examines the role of the law in Burma, suggesting that law has influenced military decision making at key points in Burma’s history. First, the right of secession granted in Burma’s 1947 Constitution accelerated military coups in 1957 and 1962, and the issue of secession will not be completely resolved until the Burmese government properly negotiates with ethnic minority groups. Second, during the heated years of 1988 to 1990, Suu Kyi’s party, the National League for Democracy (NLD), made a significant mistake when it invoked the law and proclaimed that military officials would be subject to Nuremberg-style trials. Lastly, because the junta fears the exercise of legal power against if it were to transfer legal power to civilians, the junta is extremely unlikely to cede power while its senior officials are still alive. Burma needs to learn from its past legal failures, and the elections and release of Suu Kyi provide an opportunity-if Burma chooses to take it.